Faktor internal dan eksternal kader lkb (layanan komprehensif berkesinambungan) Yang berhubungan dengan upaya pencegahan hiv/aids Di masyarakat - Andini, Yulia Putri; Dewi, Yulia Irvani; -, Jumaini - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to identify internal and external factors of LKB’s health volunteers associated to prevent HIV/AIDS disease. The methodology on this research was a correlative descriptive with cross sectional approach. The sampling technique was cluster sampling with 60 LKB’s health volunteers in Senapelan and Tenayan Raya district Pekanbaru. The measurement instrument of this research was questionnaire that have tested in validity and reliability. The univariate analysis was done to determine the distributions of frequencies dan bivariate analysis was done by using chi-square test. The results showed that there was no correlation between LKB’s health volunteers age and effort of HIV/AIDS prevention (p value = 0,181), there was a correlation between level of education and effort of HIV/AIDS prevention (p value = 0,034) and there was a correlation between knowledge and effort of HIV/AIDS prevention (p value = 0,019). It is recommended to the health care provider (puskesmas) to increase empowerment and the number of LKB’s health volunteers for maximum preventing HIV/AIDS disease. Keywords                              : Health volunteers, HIV/AIDS,  LKB, prevent